If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9k(8k + 7) = 0 Reorder the terms: 9k(7 + 8k) = 0 (7 * 9k + 8k * 9k) = 0 (63k + 72k2) = 0 Solving 63k + 72k2 = 0 Solving for variable 'k'. Factor out the Greatest Common Factor (GCF), '9k'. 9k(7 + 8k) = 0 Ignore the factor 9.Subproblem 1
Set the factor 'k' equal to zero and attempt to solve: Simplifying k = 0 Solving k = 0 Move all terms containing k to the left, all other terms to the right. Simplifying k = 0Subproblem 2
Set the factor '(7 + 8k)' equal to zero and attempt to solve: Simplifying 7 + 8k = 0 Solving 7 + 8k = 0 Move all terms containing k to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 8k = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 8k = 0 + -7 8k = 0 + -7 Combine like terms: 0 + -7 = -7 8k = -7 Divide each side by '8'. k = -0.875 Simplifying k = -0.875Solution
k = {0, -0.875}
| 10x+44=2(8x-23) | | T+4=120 | | 10-2x=-2y | | 77x^2-145+50= | | 9(x-7)+54=9x-8 | | 2(m-8)=54 | | 16-n=2n+8+5n | | 48+3x=246-15x | | 6x+4=1x-11 | | 7x-20=4x+30 | | 3(x+9)=60 | | 7+2x-10=x+2 | | 105+9.50r=14.75r | | 3x-3+5x-7=5x+3x+10 | | 3x-10=1x+4 | | 2(x+6)=-6x+2 | | 4(c+3t)=x | | 2(x-2)-54=7x-5(x+6) | | 5c^2+10x=0 | | 25=4x^2-5x-50 | | x+iy^2=-5+12i | | .09(x+5)=28 | | 3+.20x=.40 | | 11x+y=-13 | | -15-2p=1+6p | | 5+18z-2=9z+123-6z | | 8=-7t-(-8) | | 3x+12=z | | 20=l+2w | | 125*125*125-6=0 | | 2.5x-x=6 | | 12x-4=14x-8 |